IMPLEMENTASI PROGRAM POSYANDU REMAJA PADA KALANGAN REMAJA DI KELURAHAN SUDAJAYA HILIR - Neneng Yanti Andriani; Yuana Sari; Siti Nanar Aryanti; Siti Fitriya Zaenal; Yusi Yustiani; Deva Sopiawati (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2023)
3th Group of KKM III from STIE Pasim Sukabumi 2023, youth research with the establishment of the Youth Posyandu in RW 06, O7, 08 in Sudajaya Hilir Village, Baros District, Sukabumi City, West Java Province. The purpose of this study aims to bring access to knowledge closer and monitor health improvement and healthy living skills on an ongoing basis among adolescents, this becomes a reference for how much adolescents care about health. The research method used in this research is qualitative, technically using general and comprehensive observation techniques, meaning that it starts with interviews, persuasive interactions and outreach about the importance of youth posyandu. The results of this study stated that the formation of a youth posyandu in RW 06, 07, 08 Kelurahan Sudajaya Hilir can periodically influence mindsets and behavior as a form of concern for adolescents for self, family and community health.